Utilization Bound Scheduling Analysis for Nonpreemptive Uniprocessor Architecture Using UML-RT. (12th February 2014) - Pon Pushpa, S. Ewins; Devasigamani, Manamalli
Abstract : The key for adopting the utilization-based schedulability test is to derive the utilization bound. Given the computation times, this paper proposes two utilization bound algorithms to derive interrelease times for nonpreemptive periodic tasks, using a new priority scheme, "Rate Monotonic Algorithm-Shortest Job First." The obtained task set possesses the advantage of Rate Monotonic Algorithm and Shortest Job First priority scheme. Further, the task set is tested for schedulability, by first deriving a general schedulability condition from "problem window" analysis and, a necessary and sufficient schedulability condition for a task to be scheduled, at any release time are also derived. As a technical contribution, success ratio and effective processor utilization are analyzed for our proposed utilization bound algorithms on a uniprocessor architecture modeled using UML-RT.